2020
DOI: 10.3758/s13420-020-00431-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pet and detection dogs (Canis familiaris) on two aspects of social cognition

Abstract: Interspecific communication between dogs and humans enables dogs to occupy significant roles in human society, both in companion and working roles. Dogs excel at using human communicative signals in problem-solving tasks, and solicit human contact when unable to solve a problem. Dogs' sociocognitive behavior likely results from a selection for attention to humans during domestication, but is highly susceptible to environmental factors. Training for particular tasks appears to enhance doghuman communication, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 56 publications
(91 reference statements)
3
22
1
Order By: Relevance
“…However, it has been argued that comparing pet dogs to enclosure-living wolves could have biased the results of the latter study 33 . Indeed, the importance of controlling for previous experiences and exposure to humans in sociability testing cannot be emphasized enough (Two Stage hypothesis: 34 , 35 , Table 1 ; 15 , 19 , 36 , 37 . In addition, it is likely that the bond between a pet dog and its owner differs qualitatively from the relationship an enclosure-living animal may establish with its caregiver 38 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been argued that comparing pet dogs to enclosure-living wolves could have biased the results of the latter study 33 . Indeed, the importance of controlling for previous experiences and exposure to humans in sociability testing cannot be emphasized enough (Two Stage hypothesis: 34 , 35 , Table 1 ; 15 , 19 , 36 , 37 . In addition, it is likely that the bond between a pet dog and its owner differs qualitatively from the relationship an enclosure-living animal may establish with its caregiver 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, results have not been consistent across studies. For example, in Lazarowski et al ( 2020 ), human-directed gazing did not differ between dogs from cooperative working breeds (i.e., selected for working in visual contact with humans, including herding dogs and gundogs) and those with no such selective history. In addition, studies reported no difference in gaze duration in Czechoslovakian wolfdogs and German shepherds (Maglieri et al 2019 ) (nor between "wolf-like" dogs and molossoids, Passalacqua et al 2011 ).…”
Section: Introductionmentioning
confidence: 94%
“…In Marshall-Pescini et al ( 2009 ), search and rescue dogs, used to working at a distance from their owner, spent similar amounts of time gazing at the owner and the experimenter, whereas agility dogs focused significantly more on the owner than on the stranger (Marshall-Pescini et al 2009 ). In Lazarowski et al ( 2020 ), pet dogs, unlike detection dogs, gazed longer at a familiar person than at a stranger. Also, in Sanford et al ( 2018 ), pet dogs of various breeds spent on average more time gazing at the owner than at the stranger (neither of whom had interacted with the unsolvable task).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations